Effect Of Organizational Environment And Personal Factors On Work Stress And Organizational Commitment - Tah Bat, Soh (1995)
This study was conducted to examine the effect of organizational environment and personal factors on work stress and organizational commitment. Data was collected through a structured questionnaire on 104 employees in two firms, 57 from a multinational corporation (MNC) and 4 7 from a local firm.